2015
DOI: 10.1002/anie.201504013
|View full text |Cite
|
Sign up to set email alerts
|

A Reaction of Triazoles with Thioesters to Produce β‐Sulfanyl Enamides by Insertion of an Enamine Moiety into the Sulfur–Carbonyl Bond

Abstract: N-Sulfonyl-1,2,3-triazoles react with thioesters in the presence of ar hodium(II) catalyst to produce b-sulfanyl enamides in as tereoselective manner.T he reaction proceeds through generation of an a-imino rhodium carbene complex, nucleophilic addition of the sulfur atom of athioester onto the carbenoid carbon atom, and subsequent intramolecular migration of the acyl group from the sulfur atom to the imino nitrogen atom. The method is successfully applied to ar ingexpansion reaction of thiolactones,t hus leadi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
26
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 109 publications
(26 citation statements)
references
References 60 publications
0
26
0
Order By: Relevance
“…Miura, Murakami and co-workers found that ar ange of thioesters react with N-sulfonyl triazoles 71 in the presenceo fa rhodium(II) catalyst( Scheme 32). [100] The resulting b-sulfanil en-Scheme29. ChemoselectiveFukuyamar eduction of thioesters to aldehydes.…”
Section: In C(o)àsbond Cleavage and Transfer Reactionsmentioning
confidence: 99%
See 1 more Smart Citation
“…Miura, Murakami and co-workers found that ar ange of thioesters react with N-sulfonyl triazoles 71 in the presenceo fa rhodium(II) catalyst( Scheme 32). [100] The resulting b-sulfanil en-Scheme29. ChemoselectiveFukuyamar eduction of thioesters to aldehydes.…”
Section: In C(o)àsbond Cleavage and Transfer Reactionsmentioning
confidence: 99%
“…Reactionoft hioesterswith triazines catalyzedbyaR h II dimer. [100] Scheme33. Rh-catalyzed acyl transferr eaction of thioestersa nd ketones.…”
Section: In Photoredox Catalysismentioning
confidence: 99%
“…Murakami, Miura, and co‐workers reported the rhodium‐catalyzed reaction of N ‐sulfonyl‐1,2,3‐triazoles 1 with thioesters 194 to give β‐sulfanyl enamides (Scheme ) . Compared to the benzamides, the sulfur atom is more nucleophilic than the carbonyl oxygen atom.…”
Section: Reactions Of N‐sulfonyl‐123‐triazolesmentioning
confidence: 99%
“…[8] Based on the dipole feature of the in situ generated a-iminocarbene, an array of [3+ +2] cycloaddition reactions have been developed by employingu nsaturated compounds including alkynes, [9] alkenes, [10] allenes, [11] isocyanides, [12] nitriles, [13] aldehydes, [14] furans, [15] and indoles [16] as the reaction counterparts to deliver the nitrogen-containingh eterocycles. [17] More recently,t he groups of Tang, Lee, Anbarasan, Li, and Murakami have reported that enol ethers (Scheme 1a)a nd 2-(siloxy)furans (Scheme 1b)c ouldr eact with 1-sulfonyl-1,2,3-triazoles in the presence of rhodiumcatalysis to give pyrrole, lactam, and dihydropyridine derivatives. [15,18] Tang and co-workers have also described an efficient synthesis of 2,5-dihydroazepinest hrough formal aza-[3+ +2] cycloadditions of triazoles with 1,3-dienes (Scheme 1c).…”
Section: Introductionmentioning
confidence: 99%